PENGARUH KOMPETENSI APARATUR DESA DAN PARTISIPASI MASYARAKAT TERHADAP PENGELOLAAN KEUANGAN DANA DESA AUR CINA KECAMATAN BATANG CENAKU - Putri Wiji Astuti; Arttika Rahma Sari (CV. Adiba Aisha Amira, 2024)
This study seeks to explore the impact of the competence of village officials and community engagement on the financial administration of Village Funds in Aur Cina Village, Batang Cenaku District. The Village Funds, a program initiated by the Indonesian government, hold considerable potential for enhancing the well-being of rural communities by fostering infrastructure development and empowerment. However, challenges such as oversight, accountability, and the necessity for guidance and training for village officials are crucial aspects that demand attention. The research employed a descriptive methodology with a quantitative approach, involving a primary population of 10 village officials. Data collection encompassed the distribution of questionnaires, interviews, and documentation. The analysis of data involved validating and ensuring the reliability of the questionnaire, testing classical assumptions, and hypothesis testing utilizing SPSS. The findings of the research indicate that the competence of village officials, individually, exerts a significant influence on the financial management of Village Funds. Additionally, community participation demonstrates a tangible positive effect on the financial administration of village funds. The outcomes of the F- test affirm that collectively, the competence of village officials and community participation synergize to create a more optimal framework for the financial management of village funds.